Mapping Gray Matter Reductions in Obstructive Sleep Apnea: An Activation Likelihood Estimation Meta-Analysis - Weng, Hsu-Huei (Associated Professional Sleep Societies, LLC, 2014)
STUDY OBJECTIVES: The authors reviewed the literature on the use of voxel-based morphometry (VBM) in obstructive sleep apnea (OSA) magnetic resonance imaging (MRI) studies via the use of a meta-analysis of neuroimaging to identify consistent and specific structural deficits in patients with sleep apnea compared with healthy subjects. DESIGN: Neuroimaging meta-analysis. DATA SOURCES: We used PubMed to retrieve articles published between January 2000 and February 2012. STUDY SELECTION: The authors included all VBM research on patients with OSA and healthy controls. They compared the findings of the studies by using gray matter volume (GMV) or gray matter concentration (GMC) to index differences in gray matter. DATA EXTRACTION: Stereotactic data were extracted from eight VBM studies of 213 patients with OSA and 195 control subjects. RESULTS: Regional gray matter reduction in the bilateral parahippocampus and less-convincing right superior frontal and left middle temporal gyri was demonstrated in patients with sleep apnea using an activation likelihood estimation (ALE) procedure to analyze significant differences. CONCLUSIONS: Significant reductions in gray matter in patients with sleep apnea occurred in the bilateral parahippocampus and less-convincing frontotemporal regions, which may be related to the neurocognitive processing abnormalities that are common among populations of patients with sleep apnea. CITATION: Weng HH; Tsai YH; Chen CF; Lin YC; Yang CT; Tsai YH; Yang CY. Mapping gray matter reductions in obstructive sleep apnea: an activation likelihood estimation meta-analysis. SLEEP 2014;37(1):167-175.